2022
DOI: 10.1002/acp.3922
|View full text |Cite
|
Sign up to set email alerts
|

The fading affect bias is disrupted by false memories in two diary studies of social media events

Abstract: Unpleasant affect fades faster than pleasant affect, and this phenomenon is referred to as the fading affect bias (FAB). The FAB is moderated and mediated by many variables, including rehearsal and memory specificity, and researchers have emphasized the importance of memory for the FAB, but research has not evaluated the link of the FAB to objective memory measures. Using diary methodology across the span of 1 week, the current study examined the relation of event memory to the FAB for (1) social media events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Because the number of people interacting on social media is higher, the effect of the fading affect bias is expected to be faster and stronger than personally shared events (Eliseev and Marsh 2021). Interestingly, Gibbons et al (2022) found that fading effect bias is less pronounced in events shared on social media. In other words, a high rate of negative details of events recalled if the event is shared on social media (Choi andToma 2014, Gibbons et al 2017).…”
Section: The Emotional Content Of Memories Shared On Social Mediamentioning
confidence: 99%
See 3 more Smart Citations
“…Because the number of people interacting on social media is higher, the effect of the fading affect bias is expected to be faster and stronger than personally shared events (Eliseev and Marsh 2021). Interestingly, Gibbons et al (2022) found that fading effect bias is less pronounced in events shared on social media. In other words, a high rate of negative details of events recalled if the event is shared on social media (Choi andToma 2014, Gibbons et al 2017).…”
Section: The Emotional Content Of Memories Shared On Social Mediamentioning
confidence: 99%
“…The direct effect of social media on autobiographical memory is well-documented. Some studies examined the features of events recorded or shared (Comblain et al 2000, D'argembeau and van der Linden 2006, Gibbons et al 2022) while others tested the motivations (or functions) for sharing personal events on social media (Bluck and Alea 2002, Blagow and Singer 2004, Alea et al 2019. Social media posts are not independent of the sharer's self.…”
Section: Direct Effects Of Social Media Context On Autobiographical M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy and unhealthy variables measure emotional, mental, and physiological constructs that are positive, robust, and wholesome or unpleasant, undesirable, and unwanted, respectively, and these terms have been used in recent FAB studies (e.g., Gibbons & Bouldin, 2019;Gibbons, Dunlap, et al, 2022).…”
Section: Fading Affect Biasmentioning
confidence: 99%